1982
DOI: 10.1139/o82-139
|View full text |Cite
|
Sign up to set email alerts
|

Hyper(ADP-ribosyl)ation of histone H1

Abstract: Nucleosomal chains of various repeat unit lengths were generated by a mild micrococcal nuclease digestion of purified pancreatic nuclei. Maximal nucleosome associated poly(ADP-ribose) polymerase activity was recovered in trimeric to tetrameric chromatin fragments, after which the enzyme activity gradually decreased and stabilized towards oligomeric periodicities of 11 to 16 nucleosomes. Electrophoresis of [32P]ADP-ribosylated histones on first-dimension acid-urea or acid-urea-Triton gels and on second-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…Note that purified calf thymus poly(ADP-ribose) polymerase has preferentially poly(ADP-ribosyl)ated histone Hi, as previously observed with the endogenous pancreatic enzyme (11,25).…”
Section: Resultssupporting
confidence: 71%
“…Note that purified calf thymus poly(ADP-ribose) polymerase has preferentially poly(ADP-ribosyl)ated histone Hi, as previously observed with the endogenous pancreatic enzyme (11,25).…”
Section: Resultssupporting
confidence: 71%
“…For function on chromatin-remodeling regulation, it is suggested that in the presence of saturating NAD ϩ , PARP-1-dependent attachment of PARs to core histones and the linker histone H1 15,72 introduces massive negative charges and facilitates relaxation of the chromatin superstructure and recruitment of transcription machinery to the promoter or enhancer of target genes. 73,74 The literature provides evidence that the effects of PARP-1 on transcription factors regulating inflammatory cytokine gene expression vary diversely, depending on the stimuli and cell and tissue types. For example, PARP-1 has been implicated in the activation of NF-B, AP-1, and heat shock factor protein 1 transcription factors, classically known to signal inflammatory gene expression.…”
Section: Role Of Parp-1 In Inflammatory Gene Expressionmentioning
confidence: 99%
“…One of the hallmarks of the PGCs undergoing reprogramming is a transient loss of linker H1 histones [23]. In this context, PARP1 has been shown not only to replace H1 in the chromatin, but experimental evidence also shows that H1 is one of the preferred targets of PARP1 ribosylation activity and intensive ribosylation can potentially contribute to the removal/eviction of histones from the chromatin [36][37][38]. The connection between pronounced changes in chromatin compaction and the activation of PARP1 has been previously reported during the heat shock-driven transcriptional activation or in the course of DNA repair.…”
Section: Chromatin Remodelling In the Process Of Epigenetic Reprogrammentioning
confidence: 99%